Increasing Assistance to MSMEs through Training in Preparing Financial Reports at the Mandalamekar Village Youth Organization - Harry Budiantoro; Perdana Wahyu Santosa; Dean Salomo Anthonino; Nazma Riska Zhafiraah (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
Karang Taruna is a social organization as well as a forum and means for the development of every member of the community which grows and develops on the basis of social awareness and responsibility from, by and for the community, especially the young generation in the village/ district area, especially those engaged in social welfare business. Therefore, competent Human Resources (HR) are needed to produce quality financial reports. However, in reality the Financial Reports carried out by the youth organization's treasurer are still manual so this service activity is carried out to assist youth organization members in preparing financial reports that comply with accounting standards. This activity was carried out through outreach, training and mentoring to members of the youth organization in Mandalamekar Village. Based on the PKM activities that have been carried out, there were participants who were able to understand 80% of the material. Apart from that, based on the practice of making Financial Reports and how to make Financial Reports and producing four financial reports, they were arranged neatly according to what was desired and were able to present them using a laptop, not manually like before.